Sociolinguistic notes about the Tuvans in China - Bavuu-Surun, Mira V. (The New Research of Tuva, 2011)
This article describes the functions of the native (Tuvan) language of the small Tuvan community in China (about 2500 people), who are known in the scientific literature as kök-monchak, monchak, the Tuvan people of China, the Tuvan people of Xinjiang.
Keywords: Tuvan language; national minorities; social functions of language; assimilation; kök-monchak; Tuvan people of China; language influence